Public Sector Organizational Capability in Developing Religious Tourism Villages in North Sulawesi - Plangiten, Novva Novita; Londa, Very Yohanis (Universitas Padjadjaran, 2026)
Religious tourism has the potential to drive regional economic growth while strengthening cultural identity. Minahasa (regency), North Sulawesi, acquires several religious destinations of historical and spiritual value; however, their development remains constrained by the limited capability of the public sector. This study aims to analyze the organizational capability of the public sector in developing religious tourism villages, as well as to identify the opportunities and challenges involved. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with government officials, local communities, religious tourism managers, and tourism business actors, complemented by field observations and secondary document analysis. Thematic analysis was applied to interpret the data. The findings reveal that public sector capability is still at a developing stage. Planning has been directed toward integrating religious tourism into regional development programs, yet it remains short-term oriented. Key obstacles include limited resources, inadequate infrastructure, weak inter-agency coordination, and insufficient digital promotion. On the contrary, opportunities arise from the growing interest in spiritual tourism, supportive sustainable tourism policies, and the presence of villages with historical religious sites. This study contributes to the literature on local wisdom-based tourism governance and recommends strengthening planning capacity, promoting digitalization, and fostering multi-stakeholder collaboration as strategies for sustainable development.